Local institutions of culture as urban stewards: in pursuit of hybrid governance in Warsaw, Poland - Artur Jerzy. Filip (Resilience Alliance, 2020)
Since 2014, several local entrepreneurs and public institutions of culture have collaborated in transforming a central but neglected place in Warsaw, Poland: Plac Defilad (Parade Square), one of the biggest public squares in Europe. These organizations faced the challenge of taking care of their direct environment, even though they had no legal rights to it, and made efforts to get involved in local management, land-use, and place-making politics by establishing informal cross-sectoral partnership agreements. Between 2017 and 2019 the project was further developed under the conceptual framework of urban environmental stewardship as a participatory action research (PAR) program, facilitated by the author of the paper. The primary goal was to examine whether local institutions of culture could play the roles of urban stewards, and, as such, facilitate the process of creating hybrid governance structures. Only partly successful so far, the project can be seen as a precedent for more inclusive urban environmental governance policies in Warsaw. The findings of the paper highlight an underlying lack of legal vehicles and resources that would allow public institutions to form a coalition and become permanently involved in public space planning issues (that is, a contribution to stewardship practices). Furthermore, the paper argues for the need to consider the "concrete" public square an environmental issue, and for the usefulness of the conceptual framework of urban environmental stewardship for developing further research on hybrid governance initiatives in Poland (a contribution to stewardship theory).